O verbal e o não verbal em histórias em quadrinhos e manuscritos escolares criados por alunos no 2º. ano do Ensino fundamental - Ferreira, Aline da Silva (2010)
The comics are recognized by the official education (BRAZIL, 1997, 2007) and researchers defend their presence in elementary schools, based on the assumption that the verbal and nonverbal relationships that characterize contributed to student performance. We aim to understand how the relations are manifested in manuscripts school comic book Monica's Gang. For this, we characterize briefly the semiotic studies, highlighting some of the relationships between verbal and nonverbal, particularly those related to the genre in question. We then present the specifics of the "Handwriting school" as defined by Calil (2004, 2008) and the processes of creating and writing in the classroom. Data were collected from the project's educational comic book in the Hall, "developed into a class of 2nd year of elementary school of public health system in Maceio. Our corpus was formed by the set of 11 proposals take effect for 24 students, generating 131 manuscripts school. In these manuscripts we elected to analyze some typical elements of comic books (titles, shapes, visual metaphors, icons and the word "end" to the end of each story). We note that: 1) Titles, initially were not indicated, and subsequently maintained semantic relationships such as storytelling, despite not providing indications of non-verbal elements, 2) Balloons, 991 were found, indicating lines, thoughts, cries and whispers . 3) Visual metaphors were identified only 5 and 4) Icones totaled 3, 5) end, too few in number, present in only four manuscripts. There was a significant increase in the presence of visual elements throughout the development of the didactic project, although these elements are not always in accordance with the directions represented by the images provided.